782 Adverse childhood experiences affect psychological outcomes of injury in Urban black men in the US. (1st September 2016) - Richmond, Therese S; Jacoby, Sara F; Kassam-Adams, Nancy; Shults, Justine; Webster, Jessica; Robinson, Andrew; Reilly, Patrick; Rich, John; Wiebe, Douglas
Abstract : Background: Injury is not evenly distributed across race and class. In the U.S., urban Black men are at high risk for injury and poor outcomes from injury. Our purpose was to examine the contribution of adverse childhood experiences (ACEs) to post traumatic stress disorder (PTSD) and depression after recent serious physical injury in Black men. Methods: This prospective, cohort follow-up study consecutively enrolled adult Black men hospitalised for serious injury at a Level I Trauma Centre. Men with head injury or currently receiving medical treatment for PTSD or depression, and those in police custody were excluded. ACES (7) were collected by self-report during the intake interview. The outcomes of PTSD (measured by the PCL-C) and depression (measured by the QID-SR16 ) were collected during in-person interviews in the men's homes 3 months after hospital discharge. Results: 320 (mean age = 36.8 years) were enrolled. Injury was classified as unintentional (50%) or intentional, i.e. the result of interpersonal violence (50%). The mean number of ACEs did not differ between intentional and unintentional injuries (2.64 vs. 2.35, p = 0.187). 81% reported at least 1 ACE, 45% reported 3 or more ACEs and 34% reported > 4 ACEs. Intentional injuries were associated with higher mean PCL-C scores (42.4 vs. 33.7, p <0.001) and higher mean QID-SR scores (10.0 vs. 7.6, p <0.001). In adjusted multiple regressions, younger age, intentional injury, and number of ACEs were independently associated with higher PCL-C scores. Intentional injury and number of ACEs were independently associated with higher QID-SR scores. Conclusions: This sample of urban Black men reported substantial histories of childhood trauma and adversity. Results provide evidence that adverse childhood experiences increase the risk for depression and PTSD after serious injury. (Funded: NIH R01NR013503 to Dr. Richmond)